Leukopenia and thrombocytopenia in dengue patients presenting in the emergency department of a tertiary center in Nepal: a cross-sectional study - Bibechan Thapa; Prakriti Lamichhane; Trishna Shrestha; Saral Lamichhane; Shreyasi Karki; Sneha Pradhananga; Kabita Hada Batajoo; Prajwal Pudasaini (BMC Infectious Diseases)
Abstract Introduction Dengue viruses cause either symptomatic infections or asymptomatic seroconversion. Symptomatic dengue has a wide clinical spectrum ranging from self-limiting infection to severe manifestations, mostly characterized by plasma leakage with or without hemorrhage. World Health Organization classification in 2009 classified dengue into dengue without warning signs, dengue with warning signs, and severe dengue. This study aimed to determine patient characteristics and hematological parameters (leukopenia, and thrombocytopenia) in patients with dengue infection in the emergency department of a tertiary center. Methods A cross-sectional study was conducted among 252 patients with dengue confirmed by serological testing against dengue-specific nonstructural protein 1 (NS1) antigen and immunoglobulin M (IgM) by enzyme-linked immunosorbent assay from September to November 2022 who presented in the emergency department of a tertiary hospital in Nepal after ethical approval was obtained. Dengue was categorized according to the World Health Organization 2009 classification. Hematological parameters were recorded by reviewing patients’ laboratory records. Data analysis was done using descriptive statistical parameters and a chi-square test. Results Dengue without warning signs was present in 166 (65.87%) patients, while dengue with warning signs and severe dengue was present in 68 (26.89%) and 18 (7.14%) patients, respectively. Leukopenia (< 4000 cells/mm3) was present among 163 (64.68%) patients. The lowest recorded leukocyte count was 1440. Similarly, thrombocytopenia (< 150000 cells/mm3) was present among 102 patients (40.48%). The lowest recorded platelet count was 26,000 cells/mm3. A significant association was found between the severity of dengue infection and leukopenia (χ2 13.268, p-value 0.001) and thrombocytopenia (χ2 43.924, p value < 0.001). Conclusions Monitoring of warning signs and clinical parameters is important for identifying the progression of dengue infection to the critical phase. Leukopenia and thrombocytopenia are present among many dengue-infected patients presenting in the emergency department. The severity of the disease will usually only be apparent around defervescence, which often coincides with the onset of the critical phase. Leukopenia and thrombocytopenia could indicate progression to severe disease during emergency department admission.